SURVEY ON THE INCIDENCE OF SESAMIA INFERENS (WALKER) IN MAIZE IN GUNTUR AND KRISHNA DISTRICTS OF ANDHRA PRADESH - K. ANIL KUMAR*, T. MADHUMATHI, D.V. SAI RAM KUMAR, N. RAJ KUMAR; SK. NAFEEZ UMAR (The Journal of Research ANGRAU, 2023)
The cumulative results of roving survey was conducted during (rabi 2017-18 and 2018-19) in maize growing mandals of Guntur and Krishna districts for recording Sesamia inferens infestation in farmer fields.The results showed that Narasaraopet mandal recorded the least infestation by S. inferens in terms of percentage leaf infestation (18.28), dead heart percentage (15.16), stem tunneling length (2.66 cm) and found less no. of larvae (0.39 plant-1), no. of pupae (0.22 plant-1) and Battiprolu mandal recorded the least number of exit holes (0.48 plant-1). While, Ponnur mandal recorded the highest percent leaf infestation (28.05) with stem tunneling length (5.71 cm).In Krishna district, Veerullapadu mandal recorded the least infestation of maize by S. inferens in terms of percent leaf infestation (15.33), dead heart percentage (12.97), stem tunneling length (2.10 cm) and found less no. of larvae (0.24 plant-1), no. of pupae (0.18plant-1) and no. of exit holes (0.17 plant-1). Highest percentage leaf infestation (24.28) and dead heart percentage (21.26) was recorded from Mylavaram mandal;highest tunnel length (3.81 cm) from Musunnuru mandal. In case of Guntur district, highest number of spiders were recorded in Battiprolu (2.42) and least in Narasaraopet (1.39), while highest number of coccinellids were recorded in Ponnuru (4.74) and least in Battiprolu (3.54) mandals. Furthermore, more number of spiders (2.69) were recorded in Mylavaram mandal, more number of coccinellids (7.12) in Musunnuru mandal, and least number of spiders (1.18) and least number of coccinellids (2.58) in Veerullapadu mandal of Krishna district.